Seroprevalence of HBsAg, Anti-HCV and HIV in patients undergoing ocular surgery (Annals of Medical Research, 2021)
Aim: In this study, we aimed to detect the seroprevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and humanimmunodeficiency virus (HIV) in patients undergoing ocular surgery.Materials and Methods: HBsAg, anti-HCV, and HIVtestresults of patients who were admitted to the Department of Ophthalmologyof the Karabuk University Training and Research Hospital between March 2016 and April 2019 were retrospectively reviewed.HBsAg (Abbott Diagnostics, USA), anti-HCV(Abbott Diagnostics, USA) and HIV Ag/Ab Combo tests (Abbott Diagnostics, USA) wereassessed by chemiluminescence microparticleenzymeimmunoassaymethod byusingAbbottDiagnosticskits andARCHITECT i2000SR (Abbott Diagnostics, USA) immunoassayanalyzer. Patients were divided into four groups according to age: 20–39, 40–59, 60–79,and 80 years old and above. Seropositive patients were evaluated in terms of the surgical method applied.Results: Of 1504 patients included in the study, 768 (51%) were men and 736 (49%) were women, and the mean age was 70 years.HBsAg positivity was 0.79% (12/1504) and anti-HCV positivity was 2.06% (31/1504). HIV Ag/Ab Combo was negative in all patients.There were no HBsAg and anti-HCV-positive patients in the 20–39 years age group, whereasone HBsAg (0.06%) and twoanti-HCV(0.13%) positivity in the 40–59 years age group and11 HBsAg (0.73%) and 23 anti-HCV (1.52%) positivity in the 60–79 years agegroup were detected. Although HBsAg was negative in all patients over 80 years old, anti-HCV was positive in 6(0.39%) patients.Further, eight of 12 HBsAg-positive patients underwent cataracts surgery and four lacrimal canal surgery, and 24 of 31 anti-HCV-positive patients underwent cataracts surgery, five lacrimal canal surgery, and two eyelid surgery.Conclusion: All patients should be tested for HBsAg, anti-HCV, and HIV preoperatively. Seropositive patients should be informedabout viral hepatitis and should be referred to the infectious diseases department. Necessary precauti